Scale of Habitat Connectivity and Colonization in Fragmented Nuthatch Populations - van Langevelde, Frank (Ecography (Copenhagen), 2000)
Studies of effects of landscape pattern on population dynamics should consider the spatial scale at which habitat connectivity varies relative to the spatial scale of the species' behavioral response. In this paper, I investigate the relationship between the degree of connectivity of wooded patches measured at different spatial scales and the colonization of these patches by nuthatch Sitta europaea populations. I used different threshold distances to calculate the degree of habitat connectivity. A threshold distance is the distance beyond which the probability of successfully bridging the distance by dispersing individuals is assumed to decrease rapidly. The sum of the degree of connectivity over all patches in a region provides a measure for the overall degree of connectivity. Based on this measure, I could first give an indication under what conditions species may experience effects of constrained dispersal in that region. Second, the degree of connectivity of the individual patches was related with the observed colonizations of these patches. The degree of habitat connectivity measured for threshold distances of ca 2.4-3 km best explains the colonization probability of unoccupied patches. These threshold distances give an indication of the distances covered by dispersing nuthatches that led to successful colonizations.